Nested Pie Chart - Ambika Sukla; Mohit Sauhta (2005)
A pie chart divides a circle or ellipse into slices, where the size and color of each slice is based on some attributes of the elements it represents. For example, one can show the constituents of a stock porfolio in a pie-chart, where each slice will be occupied by one stock and the size of the slice will be decided by the total value of the portfolio, and the color determined by percentage price change. A Nested Pie Chart extends the functionality of a pie-chart by adding letting it represent a tree data model, thus making it a elliptical heatmap.
retrieved 26-JUL-2011